Predicting the survival probability of functional neuroendocrine tumors treated with peptide receptor radionuclide therapy: Serbian experience - Vukomanovic, Vladimir; Nedic, Katarina Vuleta; Radojevic, Marija Zivkovic; Dagovic, Aleksandar; Milosavljevic, Neda; Markovic, Marina; Ignjatovic, Vladimir; Simic Vukomanovic, Ivana; Djukic, Svetlana; Sreckovic, Marijana; Backovic, Milena; Vuleta, Marko; et al. (Frontiers in Endocrinology, 2024)
Introduction: Peptide receptor radionuclide therapy (PRRT) is a treatment option for welldifferentiated, somatostatin receptor positive, unresectable or/and metastatic neuroendocrine tumors (NETs). Although high disease control rates seen with PRRT a significant number NET patients have a short progression-free interval, and currently, there is a deficiency of effective biomarkers to preidentify these patients. This study is aimed at determining the prognostic significance of biomarkers on survival of patients with NETs in initial PRRT treatment.Methodology: We retrospectively analyzed 51 patients with NETs treated with PRRT at the Department for nuclear medicine, University Clinical Center Kragujevac, Serbia, with a five-year follow-up. Eligible patients with confirmed inoperable NETs, were retrospectively evaluated hematological, blood-based inflammatory markers, biochemical markers and clinical characteristics on disease progression. In accordance with the progression og the disease, the patients were divided into two groups: progression group (n=18) and a non-progression group (n=33). Clinical data were compared between the two groups.Results: A total of 51 patients (Md=60, age 25-75 years) were treated with PRRT, of whom 29 (56.86%) demonstrated stable disease, 4 (7.84%) demonstrated a partial response, and 14 (27.46%) demonstrated progressive disease and death was recorded in 4 (7.84%) patients. The mean PFS was a 36.22 months (95% CI 30.14-42.29) and the mean OS was 44.68 months (95% CI 37.40-51.97). Univariate logistic regression analysis displayed that age (p<0.05), functional tumors (p<0.05), absolute neutrophil count (p<0.05), neutrophil-lymphocyte ratio-NLR (p<0.05), C-reactive protein-CRP (p<0.05), CRP/Albumin (p<0.05), alanine aminotransferase-ALT (p<0.05), were risk factors for disease progression. Multivariate logistic regression analysis exhibited that functional tumors (p<0.001), age (p<0.05), CRP (p<0.05), and ALT (p<0.05), were independent risk factors for the disease progression in patients with NETs. Tumor functionality was the most powerful prognostic factor. The median PFS (11.86±1.41 vs. 43.38±3.16 months; p=0.001) and OS (21.81±2.70 vs 53.86±3.70, p=0.001) were significantly shorter in patients with functional than non-functional NETs respectively.The study's results suggest that tumor functionality, and certain biomarkers may serve as prognostic survival indicators for patients with NETs undergoing PRRT. The findings can potentially help to identify patients who are at higher risk of disease progression and tailor treatment strategies accordingly.